Museums in Dispute: Artificial Intelligence, Digital Culture, and Critical Curation - Priscila Arantes (Arts, 2025)
Museums in Dispute: Artificial Intelligence, Digital Culture, and Critical Curation analyzes contemporary debates in the museum field through the lens of tensions between technology, digital culture, and political and epistemological disputes. Structured in three parts, the article develops a critical approach that, in the first section, revisits critiques of the modernist museum model, highlighting how discourses from New Museology, institutional critique, and decolonial perspectives challenge the idea of neutral, universal, and Eurocentric museums. The second part explores the shift from temple-like museums to interface-museums, focusing on the analysis of practices such as digitization, immersive exhibitions, and gamification. It argues that while these technologies may expand access, their uncritical use can reproduce inequalities and render plural and inclusive narratives invisible. The third part addresses the emergence of hyperconnected museums and the application of artificial intelligence (AI) in curatorial, mediating, and reconstructive processes, analyzing collaborative and artistic projects such as Demonumenta and Curationist that critically reinterpret collections. Throughout the article, the concept of meta-algorithmic curation is developed, which is understood as a practice that makes algorithms visible, open to critique, and reconfigurable as cultural and political devices. Methodologically, the article combines critical theoretical review with analysis of institutional and artistic case studies, highlighting practices that appropriate the supposed neutrality of data to develop a critical pesrpective and advocate for more inclusive, distributed, and politically engaged curatorial narratives.